The Doctrine of Empirical Consciousness in the Bhoga Kārikā - Borody, Wayne Andrew (My University, 1988)
The following dissertation consists of a study of an eighth century A.D. Sanskrit text dealing with the soteriological implications of the nature of "bhoga"- "mundane experience" or, more precisely, "empirical consciousness". The dissertation can be subdivided into two major sections. The first section consists of a critical discussion or the doctrine of bhoga in the Bhogakārikāvrtti; the second section consists of an English translation of the Sanskrit text. The following study of the Bhoga Kārikā and its commentary has as its major concern the explication of the idea of "bhoga" put forth in the text. According to the school of Śaivism to which the author of the Bhoga Kārikā belongs, souls are by nature possessed of the two "capacities" (śakti) of consciousness and agency. Existing in a beginningless condition in the soul, these two capacities are obfuscated by the defiling power of a cosmic principle described as "mala". Due to this defilement the soul is forced into experiencing things in a limited manner, i.e. solely as an ego-personality whose self-understanding is both defined by and limited to the empirical sphere of experience. In explicating the doctrine of bhoga expressed by Sadyojyoti and defending his commentator Aghora Śiva, the dissertation takes up a discussion on the various polemics against other systems, such as the Buddhists, Cārvāka, Nyāya and Sāmkhya. As well, an attempt is made to point out the particular manner in which Sadyojyoti's doctrine of "bhoga" shares close affiliations with the schools of Mīmāmsā and Sāmkhya-Yoga. The text was translated under the guidance of Dr. S. S. Janaki, the Director of Kuppuswami Sastri Research Institute in Madras. The Sanskrit text of the Bhoga Kārikā consists of 146 verses by a renowned Śaivite author, Sadyojyoti (8th c. A. D.) and a brief commentary by another renowned Śaivite author, Aghora Śiva (14th c. A. D.). Although by themselves the verses are difficult to understand without the aid of the commentary, the commentary itself is written in simple Sanskrit prose. The Bhoga Kārikā is one of a host of Śaivite "manuals" that systematically define the essential teachings and particular themes of Agamic Śaivism. Aghora Śiva's commentary on the Bhoga Kārikā is typical of the commentaries accompanying most of these manuals: it is brief and polemical. Chapter I of the dissertation deals with the authors Sadyojyoti and Aghora Śiva in relation to the Śaivite tradition; as well, Chapter I treats the basic concepts of "bhoga" and "tattva" employed in the Bhoga Kārikā. Chapter II deals with the doctrine of the subtle and the gross elements, emphasizing the concern of the tattvic doctrine that each tattva is a sine qua non in the event of bhoga. Chapter III treats the sphere of the motor, sense and intellectual organs and the polemics against the Cārvākas and Nyāya concerning the role of "consciousness" in the sphere of empirical experience. The specific organs of the "antahkarana" , i.e. ,manas, buddhi and ahamkāra, are treated in Chapter IV. More epistemological issues are discussed in Chapter V, most notably the Śaivite doctrine that the soul has intrinsic to the dual capacities (śakti) of consciousness and agency. The last chapter, Chapter VI, deals with the trans-buddhi conditions governing empirical consciousness, and includes a discussion of the soteriological import of māyā and mala. Appendix I consists of the translation of the Bhoga Kārikā Vrtti while the transliteration of the text appears in Appendix II.
Keywords: Bhogakārikāvrtti; Bhoga Kārikā; empirical conciousness; bhoga; Śaivism; mala; soul; self; religion; Sanskrit